Gold(III) ions sorption on sulfur-containing polymeric sorbent based on 2, 2'-thiobisethanol dimethacrylate. Issue 12 (12th August 2020) - Ronka, Sylwia; Targońska, Sara
ABSTRACT: Studies of gold(III) ions sorption from hydrochloric acid solutions on 2, 2'-thiobisethanol dimethacrylate/ethylene glycol dimethacrylate copolymer were performed. The correlation between the concentration of HCl (0.0001–4 M) and sorption efficiency (370–140 mg g −1 ) was observed. The kinetics of sorption and the parameters of Langmuir and Freundlich isotherms for the studied systems were determined. The use of 0.8 M thiourea in 3 M HCl as eluent assured the high recovery degree of sorbed ions. It can, therefore, be concluded that newly synthesized sulfur-containing sorbent can be used in the recovery and concentration of gold(III) ions.